2019
DOI: 10.1093/noajnl/vdz020
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus seropositivity is associated with decreased survival in glioblastoma patients

Abstract: Background Human cytomegalovirus (HCMV) is an oncomodulatory human herpesvirus that has been detected in glioblastoma (GBM) and is associated with worse prognosis in patients with the disease. The effects of HCMV systemic infection on survival in GBM patients, however, are largely unknown. We aimed to determine the association between HCMV serostatus at diagnosis and survival via a retrospective cohort study of GBM patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…Our results concerning glioblastoma patients fit clinical reports proposing that glioblastoma exhibits characteristics of both cancer and neurologic diseases (42), and recently, it has been shown that HCMV seropositivity is associated with decreased survival in patients with glioblastoma (43).…”
Section: Hcmv-associated Encephalopathysupporting
confidence: 90%
“…Our results concerning glioblastoma patients fit clinical reports proposing that glioblastoma exhibits characteristics of both cancer and neurologic diseases (42), and recently, it has been shown that HCMV seropositivity is associated with decreased survival in patients with glioblastoma (43).…”
Section: Hcmv-associated Encephalopathysupporting
confidence: 90%
“…In the context of brain neoplasia, human CMV increases glioblastoma neurosphere proliferation and p-STAT3 levels, these findings suggested the existence of an association between CMV infection and STAT3-dependend modulation in glioma formation/ progression, together with tumor suppressor mutations (51). Consistent with these findings, CMV seropositivity correlates with worse prognosis in GBM patients (52). This discovery provides the basis of viral antigen targeting immune therapies in GBM.…”
Section: Non-engineered Immune Cell Approachessupporting
confidence: 61%
“…The herpesvirus's Epstein-Barr virus, herpes-simplex 1/2, has been extensively evaluated in human cancers; yet, the evidence in central nervous system tumors is contradictory [43,44]. Cytomegalovirus (CMV) was associated with glioma where serologic investigations into risk/survival and the presence of CMV within tumors have again provided inconsistent evidence of a causal link between CMV and glioma development [45][46][47][48]. However, recently two anti-CMV therapeutics have provided evidence of increased patient survival after receiving valganciclovir or a pp65 based treatment [49,50].…”
Section: Immune Related Factors: Viruses Allergy and Hlamentioning
confidence: 99%